Analysis of itb students satisfaction level towards ayam geprek ganyang - Gumilang, Muhammad Pring Ligar; Belgiawan, Prawira Fajarindra (Journal of Business and Management, 2019)
Abstract. The high demand of different culinary taste from younger generation has led to an increasing amount culinary entrepreneurial activity in Bandung City, thus resulted in an intense competition among different types of restaurants. Therefore, it is highly important for culinary businesses to manage customer satisfaction in order to compete in this sector. This study investigates particularly on ayam geprek businesses in Bandung and has taken Ayam Geprek Gayang as the main company sample. In order to analyze the customer satisfaction, four possible factors were predicted to have an affect, for instance; product quality, price, service quality and easiness. With quantitative measurement from primary, this study surveyed 231 respondents and the data are measured using multi-linear regression. The result shows that only product quality and service quality are the possible factors, as it has a significant positive correlation with customer satisfaction. Furthermore, entrepreneurs and businesses are advised to focus more on the product and service quality instead of the price and easiness in order to better improve their business activity in the future.Keywords: Customer satisfaction, product quality, price, service quality, easiness, competition, business.